(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2018)
Objectives To determine effectiveness of SNAGS Mobilization in Chronic Mechanical Low Back Pain.Design Randomized Control TrialMethodology A total of 40 patients were included as per inclusion criteria and randomly assigned into two groups each having 20 patients. Group A was given SNAG consisted of stretching and strengthening exercises while Group B was given Ultrasound consisted of stretching and strengthening exercises for 4 weeks, 3 sessions per week one session per day. The patient’s outcome measures were assessed by visual analog scale, ODI and Goniometry of Lumbar Range of Motion. Measurements were recorded before and after the end of the treatment period.